2002
DOI: 10.1007/s00330-002-1400-8
|View full text |Cite
|
Sign up to set email alerts
|

Pelvimetry and patient acceptability compared between open 0.5-T and closed 1.5-T MR systems

Abstract: time was double in the open system (7:52±1:47 vs 3:12±1:20 min). Poor image quality in the open system prevented assessment of interspinous and intertuberous diameters in one woman and all measurements in another, both pregnant, with abdominal circumferences >120 cm. The open system was much more acceptable in terms of claustrophobia and confinement (both p<0.01). Claustrophobia interrupted one closed examination. Thirty-three percent of pregnant women in both systems reported fear of fetal harm. Sixty percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…Others have compared high-field closed with low-field open MR scanners. Michel et al found poor image quality in MR pelvimetry with a low-field open MR scanner [11]. Calabrese et al concluded that open low-field contrast-enhanced MR imaging of the breast yielded good diagnostic performance in claustrophobic or oversized patients [31].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Others have compared high-field closed with low-field open MR scanners. Michel et al found poor image quality in MR pelvimetry with a low-field open MR scanner [11]. Calabrese et al concluded that open low-field contrast-enhanced MR imaging of the breast yielded good diagnostic performance in claustrophobic or oversized patients [31].…”
Section: Discussionmentioning
confidence: 99%
“…Mehdizade et al found that diffusion-weighted MR imaging performed with a low-field open MR scanner was reliable for the evaluation of acute stroke [32]. Regarding the restrictions of conventional MR imaging, horizontal open MR scanners have shown potential for facilitating imaging of patients with claustrophobia or extreme obesity [5], [7], [8], and a better patient acceptance is assumed for open MR scanners [5], [10], [11]. Reduced claustrophobia rates have also been found with recent short-bore MR scanners [2], [9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations